Seismicity and crustal structure of the southern main Ethiopian rift: new evidence from Lake Abaya - Ogden,C; Keir,D; Bastow,I; Ayele,A; Marcou,S; Ugo,F; Woodward,A; Kibret,B; Gudbrandsson,S (G3: Geochemistry, Geophysics, Geosystems: an electronic journal of the earth sciences, 2021)
The Main Ethiopian Rift (MER) has developed during the 18 Ma-Recent separation of the Nubian and Somalian plates. Extension in its central and northern sectors is associated with seismic activity and active magma intrusion, primarily within the rift, where shallow (urn:x-wiley:15252027:media:ggge22586:ggge22586-math-00015 km) seismicity along magmatic centers is commonly caused by fluid flow through open fractures in hydrothermal systems. However, the extent to which similar magmatic rifting persists into the southern MER is unknown. Using data from a temporary network of five seismograph stations, we analyze patterns of seismicity and crustal structure in the Abaya region of the southern MER. Magnitudes range from 0.9 to 4.0; earthquake depths are 0–30 km. urn:x-wiley:15252027:media:ggge22586:ggge22586-math-0002 ratios of urn:x-wiley:15252027:media:ggge22586:ggge22586-math-00031.69, estimated from Wadati diagram analysis, corroborate bulk-crustal urn:x-wiley:15252027:media:ggge22586:ggge22586-math-0004 ratios determined via teleseismic P-to-S receiver function H-urn:x-wiley:15252027:media:ggge22586:ggge22586-math-0005 stacking and reveal a relative lack of mafic intrusion compared to the MER rift sectors to the north. There is a clear association of seismicity with the western border fault system of the MER everywhere in our study area, but earthquake depths are shallow near Duguna volcano, implying a shallowed geothermal gradient associated with rift valley silicic magmatism. This part of the MER is thus interpreted best as a young magmatic system that locally impacts the geothermal gradient but that has not yet significantly modified continental crustal composition via rift-axial magmatic rifting.